Feeding Plate Fabrication for Infants with Cleft Palate Congenital Disorder at Mitra Sejati Hospital Medan and Grandmed Hospital Lubuk Pakam: Pembuatan Alat Feeding Plate untuk Bayi dengan Kelainan Bawaan Celah Langit-Langit di Rumah Sakit Mitra Sejati Medan dan Rumah Sakit Grandmed Lubuk Pakam - Chairunnisa, Ricca; Syafrinani; Rusdy, Hendry (Dentika: Dental Journal, 2022)
Cleft lip and palate (CLP) are one of the birth defects commonly found in Medan and surrounding areas with approximately 150 cases handled annually at Mitra Sejati and Grand Med Hospitals. Generally, labioplasty surgery is the only given treatment, but fabrication of the feeding plate before or after surgery is important to cover the palatal defect. From the prosthodontics aspect, fabrication after surgery cannot be performed because most parents do not know the importance of the feeding plate. To overcome this problem, community service was conducted by fabricating feeding plates that will be given 1 week after surgery. This was achieved by getting information about patients with CLP, general examination by paediatricians, the impression of the oral cavity in the operating room before surgery, outline design, and feeding plate fabrication at the dental laboratory. Subsequently, the insertion was carried out to evaluate whether infants can drink normally using a bottle. A total of 18 infants with CLP recognized the benefits of the feeding plate in Mitra Sejati and Grand Med Hospitals. The education given had a positive effect on knowledge about the importance of feeding plate and motivation for its use to make infants drink normally and gain weight according to age.